The selectivity between inner C-cyanation and alkylation in cobalt(II) complexes of N-confused porphyrin with an axial NCS− ligand. (1st February 2019) - Chen, Yi-Chun; Tung, Jo-Yu; Liu, Ta-Kang; Tsai, Wei-Joe; Lin, Chun-Yeh; Lin, Hsiang-Yin; Li, Siou-Shen; Chen, Jyh-Horung; Chang, Yu-Chang
Graphical abstract: Inner C-cyanation and alkylation were observed in the reactions of 2- N -substituted N -confused tetraphenylporphyrin (2-NCH2 YNCTPPH) with Co(SCN)2 . Abstract: Some inner C-cyanation and C-alkylation complexes have been described. Reactions of 2- N -substituted N -confused tetraphenylporphyrin (2-NCH2 YNCTPPH) with Co(SCN)2 afford C-alkylation (14 ) and C-cyanation (15 –17 ) complexes. The crystal structures for the inner C-alkylation product of thiocyanato(2-aza-2-[ p -methylbenzyl]-5, 10, 15, 20-tetraphenyl-21-benzyl-21-carbaporphyrinato- N, N ′, N ″)cobalt(II)·0.5 octane solvate [Co(2-NCH2 - p -CH3 C6 H4 -21-CH2 C6 H5 NCTPP)(NCS)·0.5C8 H18 ;14 ·0.5C8 H18 ] and the inner C-cyanation products of thiocyanato(2-aza-2-ethoxycarbonylmethyl-5, 10, 15, 20-tetraphenyl-21-cyano-21-carbaporphyrinato- N, N′, N″ )cobalt(II) [Co(2-NCH2 COOCH2 CH3 -21-CN NCTPP) (NCS);15 ], thiocyanato(2-aza-2-methyl-5, 10, 15, 20-tetraphenyl-21-cyano-21-carbaporphyrinato- N, N′, N″ )cobalt(II)[Co(2-NCH3 -21-CNNCTPP) (NCS);16 ], and thiocyanato(2-aza-2-benzyl-5, 10, 15, 20-tetraphenyl-21-cyano-21-carbaporphyrinato- N, N′, N″ )cobalt(II) [Co(2-NCH2 C6 H5 -21-CNNCTPP) (NCS);17 ] have been reported. The geometry around Co 2+ ion in these four complexes is a distorted tetrahedron with a C2v symmetry. Two possible mechanisms were proposed to explain the formation of inner C-alkylation (14 ·0.5C8 H18 ) versus C-cyanation (15 –17 ) products in these complexes with an axial * NCS − ligand.